Evolving Clinical Cancer Radiotherapy: Concerns Regarding Normal Tissue Protection and Quality Assurance - Choi, Won Hoon (J Korean Med Sci, 2016)
Radiotherapy, which is one of three major cancer treatment methods in modern medicine, has continued to develop for a long period, more than a century. The development of radiotherapy means allowing the administration of higher doses to tumors to improve tumor control rates while minimizing the radiation doses absorbed by surrounding normal tissues through which radiation passes for administration to tumors, thereby reducing or removing the incidence of side effects. Such development of radiotherapy was accomplished by the development of clinical radiation oncology, the development of computers and machine engineering, the introduction of cutting-edge imaging technology, a deepened understanding of biological studies on the effects of radiation on human bodies, and the development of quality assurance (QA) programs in medical physics. The development of radiotherapy over the last two decades has been quite dazzling. Due to continuous improvements in cancer treatment, the average five-year survival rate of cancer patients has been close to 70%. The increases in cancer patients’ complete cure rates and survival periods are making patients’ quality of life during or after treatment a vitally important issue. Radiotherapy is implemented in approximately 1/3 to 2/3s of all cancer patients; and has improved the quality of life of cancer patients in the present age. Over the last century, as a noninvasive treatment, radiotherapy has unceasingly enhanced complete tumor cure rates and the side effects of radiotherapy have been gradually decreasing, resulting in a tremendous improvement in the quality of life of cancer patients.